Deriving the Demand for a Job Guarantee from Modern Monetary Theory - Höfgen, Maurice; Ehnts, Dirk (Momentum Quarterly, 2020)
The analytical starting point of MMT is the fact that the state is the monopoly issuer of its currency. This enables the state to mobilize the resources from the private sector needed to fulfill the its public tasks. Through the level of government spending and taxation, the state decides on the extent of involuntary unemployment. From this insight, the demand for a universal job guarantee can be derived. The economic implications of the job guarantee relate to the management of the business cycle, price stability, the purchasing power of the currency and foreign trade. The social and societal implications relate to the social and psychological costs associated with involuntary unemployment, the effects on working conditions in the private labour market, a possible correction of the distribution of power between employers and employees and aspects relevant to democracy.
Keywords: Modern Monetary Theory; Job-Guarantee; Fiscal Policy; Labor Market